A systematic review of co-ethnic exposure and cardiometabolic outcomes in racial and ethnic minoritized populations - Marilyn Tseng; Ashley S. Watt; Anna K. Ostrander; Carolyn Y. Fang (Public Health Reviews, 2026)
Objectives Urban residential characteristics, including racial and ethnic composition, may be associated with cardiometabolic health. We synthesized the literature on neighborhood co-ethnic exposure and cardiometabolic outcomes among racial and ethnic minoritized populations. Methods We searched PubMed and Web of Science for studies published through October 2023 examining ethnic density or segregation and cardiometabolic conditions (adiposity, cardiovascular disease, and diabetes). Study quality was assessed using the U.S. National Institutes of Health’s Quality Assessment Tool. Results Forty-five articles representing 34 unique studies were included. Over half relied on self-reported outcomes, and nine were longitudinal. The most common exposure measure was percentage of census tract residents sharing participant’s racial/ethnic classification. Over 40% of studies including Black and Hispanic/Latine populations reported an association of greater co-ethnic exposure with poorer cardiometabolic outcomes, compared with 7% of studies including Asian populations. Across all three groups, 25%–40% of studies reported inverse associations. Conclusion Associations between neighborhood co-ethnic exposure and cardiometabolic outcomes vary both across and within racial/ethnic groups, reflecting interactions among structural (dis)advantage, community stressors, and neighborhood resources. Future research should integrate theoretical frameworks and sociohistorical context.